The effect of product quality, price, and distribution on customer satisfaction with korigengi products on Tokopedia - I Gede Fery Surya Tapa; Putu Dyah Permata Korry; Komang Sri Widiantari; Maulana Ari Danuarta (Privietlab, 2026)
The expansion of digital commerce in Indonesia has reshaped the way local creative brands compete in online marketplaces. Although platforms such as Tokopedia enable sellers to reach a wider audience, maintaining customer satisfaction has become increasingly challenging due to market saturation. KORIGENGI is a local brand specializing in otaku-themed merchandise that operates through Tokopedia, yet its competitive position remains weaker than that of several rival stores. This study aims to analyze how product quality, price perception, and distribution performance influence customer satisfaction with KORIGENGI products on Tokopedia. This research applies a quantitative approach using survey data collected from customers who have previously purchased KORIGENGI products. Structured questionnaires were distributed online and measured using a Likert scale. The collected data were examined through instrument testing, classical assumption testing, and multiple linear regression analysis. The findings indicate that product quality, price, and distribution exert positive and statistically significant effects on customer satisfaction. When examined simultaneously, these variables collectively explain the variations in customer satisfaction. Product quality was the most influential factor, followed by price and distribution. The results highlight the importance of delivering high-quality products, applying appropriate pricing strategies, and ensuring reliable distribution processes to enhance customer satisfaction in competitive e-commerce environments.